Mitogen‐activated protein kinase phosphatase‐2 deletion modifies ventral tegmental area function and connectivity and alters reward processing. (3rd February 2020) - Pytka, Karolina; Dawson, Neil; Tossell, Kyoko; Ungless, Mark A.; Plevin, Robin; Brett, Ros R.; Bushell, Trevor J.
Abstract: Mitogen‐activated protein kinases (MAPKs) regulate normal brain functioning, and their dysfunction is implicated in a number of brain disorders. Thus, there is great interest in understanding the signalling systems that control MAPK functioning. One family of proteins that contribute to this process, the mitogen‐activated protein kinase phosphatases (MKPs), directly inactivate MAPKs through dephosphorylation. Recent studies have identified novel functions of MKPs in foetal development, the immune system, cancer and synaptic plasticity and memory. In the present study, we performed an unbiased investigation using MKP‐2 −/− mice to assess whether MKP‐2 plays a global role in modulating brain function. Local cerebral glucose utilization is significantly increased in the ventral tegmental area (VTA) of MKP‐2 −/− mice, with connectivity analysis revealing alterations in VTA functional connectivity, including a significant reduction in connectivity to the nucleus accumbens and hippocampus. In addition, spontaneous excitatory postsynaptic current frequency, but not amplitude, onto putative dopamine neurons in the VTA is increased in MKP‐2 −/− mice, which indicates that increased excitatory drive may account for the increased VTA glucose utilization. Consistent with modified VTA function and connectivity, in behavioural tests MKP‐2 −/− mice exhibited increased sucrose preference and impaired amphetamine‐induced hyperlocomotion. Overall, these data reveal that MKP‐2 plays a role in modulating VTA function and that its dysfunction may contribute to brain disorders in which altered reward processing is present. Abstract : We examined whether the mitogen‐activated protein kinase phosphatase (MKP‐2) plays a global role in modulating brain function. Using MKP‐2 −/− mice, we reveal that ventral tegmental area (VTA) function and connectivity are altered, which is associated with increased excitatory drive onto VTA DA neurons but no change in VTA structure. In addition, behavioural tests indicate that MKP‐2 plays a role in reward processing. Hence, we suggest that MKP‐2 plays a role in modulating VTA function.